Pengembangan Bahan Ajar Berbasis Kearifan Lokal Padang Lawas untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV SD - Muhammad Khoiron Nasution; Sukmawarti Sukmawarti; Hidayat Hidayat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to develop Local Wisdom-Based Teaching Materials for Grade IV Elementary School Students in Padang Lawas. This study is a research and development (Research and Development) using the ADDIE development procedure consisting of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The instrument used to collect data is a questionnaire given to several expert reviewers, namely material expert reviewers, teaching material expert reviewers, teacher responses and student responses. The validation score obtained from the material expert reviewer is 90. Open material experts are 91. Teacher responses are 95.7 and student responses are 96.3. From these scores, it can be said that the Local Wisdom-Based Teaching Materials for Padang Lawas that have been developed are